2008
DOI: 10.3163/1536-5050.96.4.006
|View full text |Cite
|
Sign up to set email alerts
|

Lay information mediary behavior uncovered: exploring how nonprofessionals seek health information for themselves and others online

Abstract: LIMB may be related to gender and relationship tie strength and appears more internally than externally motivated. Further LIMB research is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 48 publications
2
97
0
Order By: Relevance
“…Help seeking appears in several bodies of literature, including information science, nursing, public health, and psychology ( Abrahamson et al, 2008;Galdas, et al, 2005;Nicholas et al, 2004;Snowden, 1998;Ybarra & Suman, 2006), and generally speaking, describes the phenomenon of an individual seeking medical / health information from the Internet or from a trusted source. Trusted sources can include both formal sources (medical professionals or counselors) or informal (peers or family), and the information being sought could be for the individual or for someone being cared for by that individual (known as Lay Information Mediary Behavior) (Abrahamson et al, 2008).…”
Section: Help Seekingmentioning
confidence: 99%
See 1 more Smart Citation
“…Help seeking appears in several bodies of literature, including information science, nursing, public health, and psychology ( Abrahamson et al, 2008;Galdas, et al, 2005;Nicholas et al, 2004;Snowden, 1998;Ybarra & Suman, 2006), and generally speaking, describes the phenomenon of an individual seeking medical / health information from the Internet or from a trusted source. Trusted sources can include both formal sources (medical professionals or counselors) or informal (peers or family), and the information being sought could be for the individual or for someone being cared for by that individual (known as Lay Information Mediary Behavior) (Abrahamson et al, 2008).…”
Section: Help Seekingmentioning
confidence: 99%
“…Trusted sources can include both formal sources (medical professionals or counselors) or informal (peers or family), and the information being sought could be for the individual or for someone being cared for by that individual (known as Lay Information Mediary Behavior) (Abrahamson et al, 2008).…”
Section: Help Seekingmentioning
confidence: 99%
“…Brashers, Goldsmith, and Hsieh (2002) reported that healthy people seek health information that reassures them of their wellness, while the sick look for information about their specific illness, treatment choices and the expected course of their infirmities. Abrahamson, Fisher, Turner, Durrance, and Turner (2008) proposed a third type of person that seeks health information on the Internet: "Lay information mediaries seek information on behalf or because of others without necessarily being asked to do so, or engaging in follow up" (p. 310).…”
Section: The Internet As a Health Informing Channelmentioning
confidence: 99%
“…Another (SR-078) commented, "It is discouraging when women are not represented at all among the senior faculty… I think it is important to have role models that are similar in gender…, even if those role models are not mentors." Most people want to seek information from people who are like them (Abrahamson, Fisher, Turner, Durrance, & Turner, 2008;Blickle et al, 2010;Harris, 2003), and junior faculty in mentoring relationships are no different. Personality also has an impact.…”
Section: Rq4: What Makes For a Successful Mentoring Relationship?mentioning
confidence: 99%